2022
DOI: 10.3390/vaccines10121990
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination in Pregnancy against Pertussis: A Consensus Statement on Behalf of the Global Pertussis Initiative

Abstract: Infants are at high risk for severe morbidity and mortality from pertussis disease during early infancy. Vaccination against pertussis in pregnancy has emerged as the ideal strategy to protect infants during these early, vulnerable, first months of life. On 30 November and 1st December 2021, the Global Pertussis Initiative held a meeting that aimed to discuss and review the most up-to-date scientific literature supporting vaccination against pertussis in pregnancy and outstanding scientific questions. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 125 publications
0
21
0
Order By: Relevance
“…Many countries have recommended Tetanus-diphtheriaacellular pertussis for women during pregnancy since 2011, [14][15][16][17] which can prevent pertussis disease in infants and is safe for both mother and fetus. [18,19] However, routine pertussis vaccination during pregnancy is not yet recommend by the Chinese Center for Disease Control and Prevention at present. In this case report, the mother did not receive pertussis vaccine during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have recommended Tetanus-diphtheriaacellular pertussis for women during pregnancy since 2011, [14][15][16][17] which can prevent pertussis disease in infants and is safe for both mother and fetus. [18,19] However, routine pertussis vaccination during pregnancy is not yet recommend by the Chinese Center for Disease Control and Prevention at present. In this case report, the mother did not receive pertussis vaccine during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The added benefit of breastfeeding in infants of vaccinated people to clinical protection is unclear. Source: Table adapted, with permission, from Abu-Raya et al 13 The GPI group concluded that there are several potential areas that require further exploration to address Tdap vaccination rates in pregnancy (Table 4). Further data on the epidemiology of pertussis infection in specific regions and countries worldwide Abbreviation: Tdap, tetanus diphtheria and pertussis vaccine.…”
Section: B Pertussis Antibodies In Breast Milkmentioning
confidence: 99%
“…We focus on obstetric and gynecologic health care providers (Ob/Gyn) and the challenges faced, in addition to potential strategies for implementing worldwide pertussis vaccination in pregnancy. Day 1 discussions, recommendations, and outcomes are available 13 About the GPIIn 2001, the GPI was initiated to: (1) increase pertussis awareness in low‐, middle‐, and high‐income countries; and (2) develop evidence‐based vaccination recommendations/strategies to decrease the disease burden in persons of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…The resurgence of the disease has prompted a short to medium-term response, leading to the incorporation of additional vaccine boosters in the adolescent and adult population, particularly in pregnant women (20,21). The data collected so far indicate that pregnant women vaccination strategy is proving successful (22,23). However, challenges persist in vaccination strategies that require resolution.…”
Section: Introductionmentioning
confidence: 99%